Is Monitoring Mean Platelet Volume Necessary in Breast Cancer Patients? - Taskaynatan, Halil (Open Med (Wars), 2018)
BACKGROUND: Mean platelet volume (MPV) is a parameter that increases during thrombotic and cardiovascular events. Tamoxifen (Tmx) and aromatase inhibitors (AIs), which are adjuvant endocrine therapies, may cause serious side effects, such as vascular thrombosis. The present study investigated the changes in MPV values of breast cancer patients receiving long-term adjuvant hormone therapy and the relationship of MPV with adverse effects of hormonotherapy. METHODS: Data of 261 patients who had pathologically confirmed estrogen or progesterone receptor positive invasive breast cancer and had received hormonotherapy for at least a 5-year period were retrospectively analyzed. MPV levels were measured at baseline and at the first and fifth year of hormone therapy. RESULTS: All patients were females and their median age was 50 years (range, 27–78 years). The mean MPV value was significantly increased in all patients in the Tmx, AI, and switch groups over time (p<0.001). CONCLUSION: This is the first study evaluating the relationship between the 5-year adjuvant endocrine therapy and changes in MPV values in breast cancer patients. Monitoring changes in MPV values may be predictive for severe side effects in breast cancer patients receiving hormone therapy.